2014 the Third International Conference on Agro-Geoinformatics 2014
DOI: 10.1109/agro-geoinformatics.2014.6910588
|View full text |Cite
|
Sign up to set email alerts
|

Spatial evaluation of crop maps by spatial production allocation model in China

Abstract: Spatial Production Allocation Model (SPAM), developed by International Food Policy Research Institute (IFPRI), is one of broadest spatial models that applied a cross-entropy method to downscale the area and yield for each crop with a resolution of 5 arc minute globally for the year 2000 and 2005.To evaluate the accuracy of three staple crops (rice, wheat and maize) in China allocated by SPAM, we compared these crop maps with remote sensed cropland derived from national land cover datasets. This is done through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Using a classic cross-entropy approach, the SPAM makes plausible allocations of crop production in geopolitical units (country or state) into individual pixels through judicious interpretation of all accessible evidence such as production statistics, farming systems, satellite images, crop biophysical suitability, crop prices, local market access, and prior knowledge. e 5-by-5-minute resolution maps obtained with the SPAM for major crops agreed well with validated groundbased results [44][45][46]. e MODIS land cover data includes 17 land cover types: 11 natural vegetation classes, 3 developed and mosaicked land types, and 3 nonvegetated land types [47].…”
Section: Calculation Of Heat Wave Index and Wheat Pixelsupporting
confidence: 68%
“…Using a classic cross-entropy approach, the SPAM makes plausible allocations of crop production in geopolitical units (country or state) into individual pixels through judicious interpretation of all accessible evidence such as production statistics, farming systems, satellite images, crop biophysical suitability, crop prices, local market access, and prior knowledge. e 5-by-5-minute resolution maps obtained with the SPAM for major crops agreed well with validated groundbased results [44][45][46]. e MODIS land cover data includes 17 land cover types: 11 natural vegetation classes, 3 developed and mosaicked land types, and 3 nonvegetated land types [47].…”
Section: Calculation Of Heat Wave Index and Wheat Pixelsupporting
confidence: 68%
“…MapSPAM data is extensively evaluated by several institutions for plausibility (see You et al 2014b), yet these evaluations were mainly qualitative or semi-quantitative in nature. We are only aware of one independent and quantitative assessment of the MapSPAM data by Tan et al (2014), who compared the accuracy of the crop maps with empirical case study results for China and found a satisfactory agreement. Regarding the FAO trade data, we rely on the data from Kastner et al (2014) that circumvents the common problem of bilateral trade data by tracing the primary origin of imported agricultural produce, linking crops to their actual places of consumption.…”
Section: Caveats Of the Allocation Algorithmmentioning
confidence: 99%